How competitive environments shape career progression in youth football: Context-dependent influence of geographical proximity to U19 Bundesliga teams and professional clubs - Simonn, F. C.; Nasser, G. (Journal of Sports Sciences, 2026)
Adopting an ecological perspective that considers geospatial competition as a central contextual factor in talent development, this study investigates how proximity to other elite U19 teams and professional clubs relates to the transition of German youth football players to the professional level. Utilizing data from 1411 players who accumulated substantial playing time in the A-Junioren Bundesliga, we applied mixed-effects logistic regression models to analyse whether (a) the average distance to other U19 Bundesliga teams and (b) the distance to the nearest Bundesliga or 2. Bundesliga club serve as predictors for professional debuts within three seasons after the U19 career period. Our results indicate that, for players from top-tier clubs, shorter distances to U19 teams are associated with a higher likelihood of debuting in the Bundesliga, while greater proximity to Bundesliga or 2. Bundesliga clubs isassociated with a lower likelihood of such debuts. Conversely, for players from lower-tier clubs, greater geographical remoteness from U19 competitors and closer proximity to a Bundesliga or 2. Bundesliga are associated with higher odds of progressing to the 2. Bundesliga. These findings suggest that club officials should consider regional competitive context in recruitment, and encourage researchers to further examine geospatial influences on talent development pathways.